ANALYSIS OF ABDULKHALIQ GIJDUVANI’S WORK “MAQOMOTI YUSUF HAMADONI” (Scientific journal of the Fergana State University, 2026)
This article discusses Abdulkhaliq Gijduvani and analyzes his work dedicated to his teacher Yusuf Hamadoni - “Maqomoti Yusuf Hamadoni”. The article highlights that, alongside valuable information about the life and activities of Yusuf Hamadoni, there are also some problematic points, and the author presents his own perspective on the reasons for their occurrence.